Design and Validation of the Fractal Model of Virtual Curriculum with an Intercultural Approach (Case Study: Islamic Azad University Branches in Mazandaran) - Shahabi Moghadam, Parvaneh; Rasouli, Seyede Esmat; Salimi, Ladan (International Journal of Education and Cognitive Sciences, 2025)
Purpose: This study aimed to design and validate the Fractal Model of Virtual Curriculum with an Intercultural Approach in the context of Islamic Azad University branches in Mazandaran. Methods and Materials: The research employed a mixed-methods approach consisting of qualitative and quantitative phases. In the qualitative phase, data were collected through semi-structured interviews with 16 experts in curriculum studies, online education, and intercultural knowledge, using snowball sampling. Data analysis followed inductive content analysis, including open, axial, and selective coding. In the quantitative phase, a 92-item questionnaire was developed based on the qualitative findings and administered to 250 undergraduate, master's, and doctoral students in educational sciences at Islamic Azad University, selected through stratified random sampling. Data analysis was conducted using structural equation modeling (SEM) in SMART-PLS, with validation performed through exploratory and confirmatory factor analysis. Findings: The validated model consisted of nine elements: objective, content, learning activities, teaching-learning strategies, space, time, grouping, educational materials, and evaluation, with 23 subcomponents. Path analysis showed that all relationships between elements were statistically significant (p < 0.001). The strongest relationships were observed between learning activities and collaborative activities (β = 0.900), time and instructional time suitability (β = 0.932), and grouping and multicultural teams (β = 0.890). The KMO values for all elements confirmed sampling adequacy, and Bartlett’s test indicated the feasibility of factor analysis. Conclusion: The findings emphasize the need for inclusive educational strategies, flexible digital learning environments, and multicultural assessment methods to enhance the effectiveness and equity of online curricula in higher education